Antidiabetic Effects of Moringa oleifera Leaf Extract on Blood Glucose Levels in Alloxan-Induced Diabetic Rats (Rattus norvegicus): A Systematic Literature Review - Harahap , Armansyah Maulana; Ginting, Muhammad Aldi Rivai; Putri, Yulia; Sari, Herviani; Priawan, Indra (CoinReads Media Prima, 2025)
Introduction: This systematic literature review, guided by PRISMA guidelines, evaluates the effectiveness of Moringa oleifera leaf extracts in reducing blood glucose levels in alloxan-induced diabetic rats. Method: Literature was searched in PubMed and Google Scholar using keywords including “Moringa oleifera,” “leaf extract,” “alloxan-induced diabetes,” and “blood glucose.” From 472 identified articles, 9 studies met inclusion criteria and were analyzed. Results: Nearly all studies reported significant reductions in blood glucose levels following administration of Moringa oleifera leaf extracts at effective doses ranging from 200–800 mg/kg body weight over 14–28 days. Key mechanisms include protection of pancreatic β-cells from oxidative stress, enhanced insulin secretion, and improved insulin sensitivity. Both aqueous and ethanolic extracts exhibited antihyperglycemic effects, with aqueous extracts demonstrating faster onset and ethanolic extracts providing more sustained outcomes. Conclusion: These findings support the potential of Moringa oleifera leaf extracts as a natural antidiabetic agent in preclinical models. However, further research is required to standardize extraction methods, dosages, and molecular mechanisms to facilitate clinical translation in humans.